The Effect of Strengths-Based Performance Appraisal on Perceived Supervisor Support and the Motivation to Improve Performance - van Woerkom, Marianne; Kroon, Brigitte (Frontiers in Psychology, 2020)
Strengths-based performance appraisal focuses on identifying, appreciating, and developing employee’s qualities in line with the company goals. In this study, we investigated to what extent strengths-based performance appraisal is associated with higher levels of perceived supervisory support, and in turn a higher motivation to improve performance. We distributed a questionnaire to employees working for a large Dutch consultancy firm right after their yearly appraisal (N = 422) and linked the questionnaire data to their official performance ratings. Conditional process analysis indicated that strengths-based performance appraisal had a positive effect on perceived supervisor support, and in turn on motivation to improve performance. Furthermore, the effect of strengths-based performance appraisal was particularly strong, when the performance rating was relatively low. Our findings indicate that a focus on strengths in the performance appraisal may boost employees’ optimism regarding future successes, which is especially important to safeguard a supportive relationship with the supervisor when the performance rating is relatively low.